Psychological Help-Seeking Attitude and Locus of Control among College Student - Muna Al-Bahrani (Sultan Qaboos University, 2014)
This study investigated psychological help-seeking attitude and its relation to gender, year in college, accommodation, and locus of control among college students. A total of 152 students (55.3% female and 44.7% male) participated in this study. Self-report data on psychological help-seeking attitude and locus of control scale were assessed. Results showed participants held positive attitude towards help-seeking. Help-seeking attitude did not vary by gender, year in college, and accommodation. Significant contribution attributed to locus of control. Externally locus of control type participants indicated more positive help-seeking attitude than internally type.